Rancang Bangun Sistem Pemberian Pakan Ikan Secara Otomatis Berdasarkan Perilaku Ikan Menggunakan Kamera Berbasis Mini PC - Yuni Marliza; Ratna Aisuwarya (CHIPSET, 2021)
This research was conducted because fish feeders are often forgotten by fish owners, so the researchers created an automatic fish feeding system using the Raspberry Pi, Camera Module-v2, Accelerometer Sensor, and Servo Motor. The way this tool works is the reading of water ripples carried out by the accelerometer sensor which later can get a trigger value to turn on the camera module-v2 and take pictures of the fish, the resulting image will be processed to identify the fish's mouth and calculate the number of fish mouths that appear to the surface. When the system can detect the number of fish mouths, the fish is hungry and the servo motor will open the food valve to release the fish food, but when the number of fish mouths is 0 or not detected, the servo motor will not open.